Plasma-sprayed human bone-derived hydroxyapatite coatings: effective and reliable - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
Human bone-derived hydroxyapatite (HHA) was used as plasma-spraying powder in this study. The starting powder was derived with the calcination method as described in recent literature. There have been very few researchers who were seriously interested in calcined HHA as a grafting material. Instead, demineralized HHA (from other humans) was usually preferred among surgeons. This brings some possible danger of transmission of infectious diseases like hepatitis B and C, human immunodeficiency virus (HIV), and almost incurable prion diseases like Creutzfeldt-Jakob disease (CJD) and bovine spongiform encephalopathy (BSE). Due to very high temperature application (850 degreesC), calcined HA seems to be safe and promising as an alternative product to other HA materials in the biomaterial market. As it is known, HA is very weak at load-bearing applications. To overcome this weakness, it is suggested to use it as a coating on metallic substrates. The HA plasma spraying process is a well-known process for such durable coatings. In addition, in order to gain higher strength, it is recommended to use a very thin bond-coating layer to prevent the mismatch of the thermal coefficients between metal and ceramic. Bond coatings are used very widely in industrial applications. Some biomedical bond-coating research has been conducted, but the reports are not yet commercialized. In this study, tensile strength, SEM and X-ray diffraction studies were performed. Bonding strength was found to be 6.91 MPa for nonbond-coated and 13.15 MPa for bond-coated HHA coatings. These results indicate that the application of bond coating with HHA had strengthened the structure of this material. The X-ray diffraction analysis showed a relatively high crystalline phase. SEM pictures indicate very good adhesion of the bond coating on the metal and on the main coating. The production of HHA with the calcination method is economic, and the resulting material (in combination with plasma spraying) can be used for bone grafting purposes. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: human-derived hydroxyapatite; calcination; plasma spraying; bond coating; bone grafts; transmitting infectious diseases; economic; MECHANICAL-PROPERTIES; RECONSTRUCTION; COMPOSITES; DENTIN